Scholarly sport sites
This subject directory brings together the websites which will assist the serious sports researcher, kinesiology librarian, sport information specialist, college/university student and faculty. An Index to Sport Subjects provides the access to the specific parts of this website. When viewing the major subject areas, e.g. Associations, look for notes on contents under the major subject heading. Some listings are annotated when specific features need emphasis. Websites for pro sports, many sport-specific organizations and commercial sport sites, local sport clubs and teams have not been listed or have been given only brief attention. These websites are easily found by the avid web surfer using the many single, multi-search engines, the many subject-specific directories listed here under the subject, DATABASES/DIRECTORIES